2010
DOI: 10.1007/s00264-010-0957-0
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of severe scoliosis with high risk pulmonary dysfunction in Duchenne muscular dystrophy: patient function, quality of life and satisfaction

Abstract: In a previous study, the authors reported the clinical and radiological results of Duchenne muscular dystrophy (DMD) scoliosis surgery in 14 patients with a low FVC of <30%. The purpose of this study was to determine if surgery improved function and QOL in these patients. Furthermore, the authors assessed the patients' and parents' satisfaction. %FVC increased in all patients after preoperative inspiratory muscle training. Scoliosis surgery in this group of patients presented no increased risk of major complic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 22 publications
0
19
0
3
Order By: Relevance
“…Qualitative data studying the impact of surgical correction for patients and parents showed that surgery had improved function, sitting balance and quality of life (74). The long-term effects of surgery on respiratory function are controversial as different researchers have found differing results.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative data studying the impact of surgical correction for patients and parents showed that surgery had improved function, sitting balance and quality of life (74). The long-term effects of surgery on respiratory function are controversial as different researchers have found differing results.…”
Section: Discussionmentioning
confidence: 99%
“…28,104,105 Posterior spinal instrumentation and fusion are recommended in non-ambulatory individuals who have a spinal curve in the sitting position greater than 20-30°, who have not yet reached puberty, and who have not been treated with corticosteroids because the curve is expected to progress. Although patients treated with corticosteroids can still develop scoliosis, the progression might be less predictable, so observation for clear evidence of progression is a reasonable approach before intervening.…”
Section: Orthopaedic and Surgical Managementmentioning
confidence: 99%
“…Three studies190–192 compared the rate of decline of vital capacity before and after surgery in the same individuals; five studies172 193–196 compared the rate of decline to a non-operated group comprised either of children who did not yet need surgery, children in whom surgery was considered too high risk, or children who refused surgery; and five studies26 179 197–199 compared a single preoperative mean vital capacity to one taken 2 or more years after surgery. Eight of the studies26 172 179 190 192 194 198 199 indicate that the rate of decline of vital capacity was reduced after surgery, or that vital capacity was maintained close to preoperative levels. Five studies191 193 195–197 found that the rate of decline of lung function was unaffected by surgery or was the same as that in a control group.…”
Section: Scoliosismentioning
confidence: 99%